Food choices of African Americans compared to other racial/ethnic U.S. populations using NHANES, 2003-2006, dietary survey data - Hightower, Carrita A. (Kansas State University, 2010)
Food consumption continues to be an area of focus for nutrition, health, and consumer research. Eating adequate amounts of fruits and vegetables, appropriate levels of dairy products, increasing whole grains, and switching to lean meat and fish all are associated with managing weight and reducing the risk of chronic diseases including cancer, diabetes, hypertension, and cardiovascular disease. Research has shown that food consumption rates vary across segments of the U.S. population depending on several socio-demographics including race/ethnicity, gender, and age. The purpose of this research was to examine consumption of various foods including fruits and vegetables, dairy products, selected types of grain and starchy vegetable foods, and meat and legume products based on race and ethnicity, age, and gender using 24-hour recall dietary data from survey years 2003-2006 of the National Health and Nutrition Examination Survey (NHANES) conducted by the Centers for Disease Control and the United States Department of Agriculture. The 2003-2006 NHANES 24-hour dietary recall data, known as What We Eat In America, were used for analysis of food consumption. Two non-consecutive days of 24-hour dietary recall and demographic information were analyzed to assess consumption patterns of participants who: 1) were at least two years of age, 2) had complete and satisfactory dietary recall data, and 3) were members of a selected racial/ethnic group. The sample size was 17, 885 males and females: 4,994 African Americans (non-Hispanic); 7,525 Whites (non- Hispanic); and 5,366 Hispanics (Mexican American and other Hispanics). Individual Foods Files (IFF), containing foods coded for each individual, were accessed via the NHANES website to use for the consumption comparison analysis. There were food files for each of the two recall days of each survey year, 2003-2004 and 2005-2006. These findings indicate that there are racial/ethnic, age, and gender differences in the consumption of various foods. Fruits, vegetables, and dairy products were only consumed by 70-80% of the sample populations. Only 18-42% of the respondents reported eating whole grain breads, legumes, nuts, and seeds. However, meat and meat product consumption was reported by more than 75% of the sample. African Americans consumed fewer fruits, vegetables, whole grains, and dairy products compared to Whites and Hispanics. African Americans had a tendency to consume culturally relevant items such as greens, sweet potatoes, grits, and chicken. Children consumed more French fries, frankfurters, peanut butter, macaroni and cheese, and hamburgers than adults. Consumption rates among males and females depended on race/ethnicity. However, within a racial/ethnic group, gender consumption differences were minimal. This research demonstrates that the types of foods eaten for all groups of food products vary by racial and ethnic population, and age or gender subgroups. African Americans' fruit and vegetable consumption trends are distinct in many cases. This research serves as a current baseline for future research exploring the relationship of dietary intake and race and ethnicity. Given that African Americans have higher incidences of chronic diseases, there is a need to continue to develop culturally sensitive dietary counseling and intervention programs. Furthermore, this study highlights areas of opportunities to expand research involving African Americans from a sensory, business and promotional perspective capitalizing on the diversity of food habits.
Keywords: African American; Consumption; Diet; Food; Hispanic; National Health and Nutrition Examination Survey- NHANES; Health Sciences, Nutrition (0570)